2018
DOI: 10.1016/j.eururo.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Pembrolizumab in Second-line Advanced Bladder Cancer

Abstract: This article assessed the cost-effectiveness of pembrolizumab for the treatment of patients with metastatic bladder cancer who had previously failed one treatment regimen. It would cost $122 557 in the United States, $91 995 in the United Kingdom, $90 099 in Canada, and $99 966 in Australia to gain one quality-adjusted life-year with pembrolizumab versus chemotherapy in these patients, which may be considered cost-effective only in the United States because of the differences in willingness-to-pay thresholds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…Sarfaty et al [25] recently reported on the costeffectiveness of pembrolizumab as second-line therapy for advanced urothelial carcinoma. However, their study ICER = incremental cost-effectiveness ratio; RPSFT = rank-preserving structural failure time; LY = life years; QALY = quality-adjusted life years; P/D/ = paclitaxel/ docetaxel; P/D/V = paclitaxel/docetaxel/vinflunine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarfaty et al [25] recently reported on the costeffectiveness of pembrolizumab as second-line therapy for advanced urothelial carcinoma. However, their study ICER = incremental cost-effectiveness ratio; RPSFT = rank-preserving structural failure time; LY = life years; QALY = quality-adjusted life years; P/D/ = paclitaxel/ docetaxel; P/D/V = paclitaxel/docetaxel/vinflunine.…”
Section: Discussionmentioning
confidence: 99%
“…The RPSFT adjustment method was the second best method in this scenario. was subject to limitations of data availability and suboptimal modeling methods for survival, utility, and costs [20,25]. Our analysis has several strengths that explain the difference in results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there appears to be uncertainty in the cost-effectiveness of pembrolizumab. A 2018 analysis by Sarfaty et al, based off data from KEYNOTE-045 determined that for this indication relative to chemotherapy pembrolizumab did not produce the quality-adjusted life years (QALY) gains at a willingness-to-pay threshold of $100,000 in the U.S. [ 79 ]. QALY is a measure of the incremental health improvement provided by a new treatment compared to previous treatment options.…”
Section: Health Economic Factorsmentioning
confidence: 99%
“…Cost-effectiveness studies derived from the KEYNOTE-045 study show that the cost of pembrolizumab to gain one quality-adjusted life-year is $122, 557 in the US, which is higher than the cost in other developed countries, but it is considered cost-effective only in the US because of significantly higher threshold for willingness-to-pay. 45 Based on the studies, pembrolizumab is also considered as cost-effective, first-line treatment for NSCLC when compared to other chemotherapies that express high levels of PD-L1 with TPS ≥50%. 46 Such studies are not yet available for gastric or GEJ cancers.…”
Section: Introductionmentioning
confidence: 99%